A novel method for solving fuzzy parabolic PDE by using the SG-Hukuhara differentiability - Pegah Moatamed; Mahnaz Barkhordari Ahmadi (Journal of Mahani Mathematical Research)
In this paper, the method of Crank-Nicolson is proposed for approximating the solution of  a fuzzy parabolic PDE by applying the subject of  SG-Hukuhara differentiability where the initial and boundary conditions are fuzzy numbers. The consistency and stability of this method are investigated and finally,  a non-trivial example is given by this method.